2021
DOI: 10.3389/fnins.2021.663980
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C as a Potential Predictor of the Severity of Multiple System Atrophy With Predominant Cerebellar Ataxia: A Case-Control Study in Chinese Population

Abstract: Objective: Multiple system atrophy (MSA) is a serious neurodegenerative disease that is charactered by progressive neurological disability. The aim of this study was to investigate the correlation of serum oxidant factors with the severity of MSA.Methods: A total of 52 MSA patients and 52 age- and gender- matched healthy subjects were retrospectively enrolled in this study. Enzymatic colorimetric methods were used to assay the concentrations of uric acid (UA), serum creatinine (Scr), blood urea nitrogen (BUN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Our finding that cystatin C levels were significantly higher in patients with MSA than in HCs, which was consistent with a previous case–control study in Chinese population ( Ye et al, 2021 ). We observed a significant cognitive decline in patients with MSA after a 1-year follow-up, which was supported by our previous study ( Zhang et al, 2022a ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that cystatin C levels were significantly higher in patients with MSA than in HCs, which was consistent with a previous case–control study in Chinese population ( Ye et al, 2021 ). We observed a significant cognitive decline in patients with MSA after a 1-year follow-up, which was supported by our previous study ( Zhang et al, 2022a ).…”
Section: Discussionsupporting
confidence: 93%
“…Our recent study observed a significant cognitive decline in patients with MSA after a 1-year follow-up ( Zhang et al, 2022a ). Cystatin C was found to be associated with the disease severity in patients with MSA ( Ye et al, 2021 ). However, the association between cystatin C and cognitive decline in patients with MSA remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies found that plasma CysC levels of ALS patients was significantly increased and CysC levels in cerebrospinal fluid (CSF) was significantly decreased compared with healthy controls (HCs; Wilson et al, 2010;Zhu et al, 2018); some studies found no significant difference in the serum CysC level between ALS patients and controls (Tetsuka et al, 2013;Ren et al, 2015). Additionally, our previous study found CysC may be correlated with a decline in the cognitive function of patients with AD and multiple system atrophy (MSA; Chen et al, 2021;Zhang et al, 2022), as well as with the severity in MSA patients (Ye et al, 2021). However, other studies showed that serum CysC level was related to the disease severity and site of onset (Ren et al, 2015), as well as survival in ALS patients (Zhu et al, 2023), in contrast with some studies with negative findings (Tetsuka et al, 2013).…”
Section: Introductionmentioning
confidence: 91%